China diverges from global trends in a 30 year comparative analysis and future projections of ischemic heart disease burden attributable to high LDL cholesterol - Jianing Liu; Kai Wang (Discover Public Health)
Abstract Background Ischemic heart disease (IHD) remains a leading cause of morbidity and mortality worldwide, with high low-density lipoprotein (LDL) cholesterol as a key modifiable risk factor. However, the burden of IHD attributable to high LDL cholesterol in rapidly developing countries like China, which has undergone significant economic and lifestyle changes, remains unclear. This study aims to compare the trends in IHD burden attributable to high LDL between China and global levels. Methods Using the latest data from the Global Burden of Disease (GBD) 2021 study, we analyzed trends in IHD-related disability-adjusted life years (DALYs) attributable to high LDL cholesterol in China and globally from 1990 to 2021. Joinpoint regression, Age-Period-Cohort (APC) models, and autoregressive integrated moving average (ARIMA) model were used to assess trends and project future burden. Results From 1990 to 2021, China’s age-standardized DALY rate for IHD attributable to high LDL cholesterol slightly increased from 568.2 (95% UI: 375.78 to 748.75) to 585.1 (95% UI: 377.57 to 805.62) per 100,000, while globally, the rate decreased from 1141.43 (95% UI: 789.59 to 1482.57) to 776.69 (95% UI: 551.21 to 1011.18) per 100,000. China’s estimated annual percentage change (EAPC) was 0.42, contrasting with the global EAPC of − 1.39. Projections suggest China’s DALY rates will remain stable over the next 15 years, while global rates will decline significantly. Conclusion Despite global reductions in IHD burden, China’s stagnant trend highlights the need for more targeted public health interventions to address rising cardiovascular risks driven by rapid urbanization and lifestyle changes.